Fasciola hepatica cathepsin L1 from a Turkish isolate is related to Asiatic isolates - Kuk, S; Kaplan, M; Ozdarendeli, A; Tonbak, S; Felek, S; Kalkan, A (Springer Int Publ Ag, 2005)
Cathepsin L1 (CatL1) is one of the major molecules in the excretory-secretory products of Fasciola hepatica and is secreted by all stages of the developing parasite; it is involved in tissue penetration, immune evasion, feeding and pathogenesis. Our aim in this study was to clone and characterise the F hepatica CatL1 gene from a Turkish isolate. This is the first report of cDNA encoding CatL1 protein of F hepatica from a Turkish isolate. Phylogenetic analysis based on the CatL1 showed that the Turkish isolate is genetically related to Asiatic isolates. The cathepsin L1 gene may be used for DNA vaccination and recombinant protein derived from the gene can be used for serological diagnosis against F hepatica in Turkey.
Keywords: Fasciola hepatica; cathepsin L1; cloning; sequencing; phylogenetic analysis